Regional Economic Growth in Mexico : Recent Evolution and the Role of Governance - Weiss, Eli; Rosenblatt, David (2012)
There has been substantial research in recent years examining the regional evolution of economic growth across states in Mexico -- with a particular focus on the post North American Free Trade Agreement period. There is also a vast literature using cross-country regressions to examine institutional determinants of economic growth, including government transparency, or "corruption," as a key institutional variable. This paper uses more recently available data for Mexican states to both update the general state convergence/divergence literature, and incorporate into the analysis more recently developed state level indicators of institutional factors related to government transparency. The authors do not find a systematic relationship between measures of government transparency and gross domestic product per capita growth in Mexico during 2001-2005; however, they do find that corruption is negatively associated with the level of state gross domestic product per capita. The contrasting results may imply that more years of data are necessary to be able to establish statistically significant relationships between state growth rates and measures of corruption.